La littérature et la légende comme motifs touristiques en Espagne au xxie siècle - Christelle Schreiber-Di Cesare (Cahiers de Civilisation Espagnole Contemporaine)
Having become the world's second most popular tourist destination, Spain has long been content to develop its coastline to accommodate tourists who are essentially looking for sun and beach. The massification of tourism, the destruction of natural areas by property speculation and the growing competition from other countries have shown the limits of this model and Spain, having acquired international visibility with the Barcelona Olympic Games in 1992, decided to implement tourism strategies linked to other territories than just the coastlines, in order to give it a more modern image, to show the diversity of its resources and to welcome visitors all over the country, throughout the year. This has led to the development of cultural tourism, which aims to show the heritage of a territory and the way of life of its inhabitants. It includes various activities, such as visiting natural sites, monuments or museums, discovering gastronomic specialities or participating in events such as exhibitions or concerts. This study focuses on tourism based on Spain's literary heritage: the organisation of book fairs, the opening of writers' houses and museums, the setting up of literary tours in the footsteps of an author or a work, public authorities and private initiatives are multiplying strategies to both create and respond to the demand from a public that wishes to extend the reading experience with a foray into the settings of the plot. The last part of this analysis will be devoted to the tourism of tales and legends, which is attracting more and more visitors, notably due to the growing success of themes such as witchcraft or zombies.